Tāwakewake : an historical case study and situational analysis of Ngāti Ruawaipu leadership : a thesis presented for the degree of Doctor of Philosophy in Māori Studies at Massey University, Albany, Aotearoa-New Zealand - Kohere, Rarawa (Massey University, 2005)
This thesis, Tāwakewake,¹ is a case study about decision making protocols adopted by Ngati Ruawaipu. It examines decision making pathways and the significance of intergenerational transmission of knowledge from whare wānanga and whare kura. Decision making is explored through a range of themes derived from cosmological, theological, and anthropological domains of Te āo Māori. Emanating from these themes five states of potentiality are identified: Te Ihowai Te Wehi, Te Mana, Te Ihi, and Te Mākurangi. They are used to map the long journey of a Ngati Ruawaipu history of struggle to resolve hapu and whanau issues of power and safety. A framework, Tāwakewake, based on the writings of the theorist Nēpia Pohohū - a descendant of Tīhaere, Tamaihu, and Hinepare and a guardian of Ngati Ruawaipu knowledge - incorporates key elements of Ngati Ruawaipu mediation (utu) and moderation (hoko), their impact on decision making, and their subsequent socialisation (manaakitanga). In this way, a situational analysis details strategies and measures Ngati Ruawaipu took to counter hegemonic processes in defence of takiwa, moka, and kainga. In drawing upon a range of testimonies, reports, and archival material, the work brings together the lived experiences of an historical sampling of people to land, and people to people interactions. The need to connect passive modes of engagement with land and with people, into pro-active forms of participation based on Ngati Ruawaipu traditions and world views is highlighted. (Refer to Appendix 2 for Māori synopsis). ¹Tawakewake - Taken from the taniko border of Mokena Kohere's korowai. According to Te Ao Wiremu, in 1986, Tāwakewake meant ‘to resolve issues between domains’.
Keywords: Maori; Politics and government; Social life and customs; Leadership; Ngāti Ruawaipu; New Zealand; Māori Doctoral Thesis